Diaphragm modifier, high-wettability diaphragm as well as preparation method and application of high-wettability diaphragm

By using natural mineral clay sheets, one-dimensional conductive polymer materials and MXene composite material modifiers in the separator, the problems of insufficient conductivity, hydrophilicity and mechanical properties of the existing separator are solved, and the demand for high energy density and long-circulation batteries is achieved, while reducing production costs.

CN119786877APending Publication Date: 2025-04-08XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411994524.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing separators have no outstanding electrical conductivity, hydrophilicity and mechanical modification, which cannot meet the needs of high-energy and high-power density batteries, and the modification cost is high.

Method used

Natural mineral clay sheets, one-dimensional conductive polymer material and MXene are mixed to form a composite membrane modifier and coated in the middle area of ​​the base film to improve the conductivity, wetting and mechanical properties of the membrane.

Benefits of technology

The high conductivity, wetting and mechanical properties of the diaphragm are improved, meeting the needs of high energy density and long-circulating batteries, while reducing production costs and simplifying the coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786877A_ABST
    Figure CN119786877A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a diaphragm modifier, a high-wettability diaphragm as well as a preparation method and application of the high-wettability diaphragm, and the diaphragm modifier comprises a natural mineral clay sheet, a one-dimensional conductive polymer material and MXene. According to the high-wettability diaphragm disclosed by the invention, the diaphragm modifier is adopted to modify a base membrane, so that the requirements of high-energy-density and high-power-density batteries can be met, the long-term use requirements of the batteries can be met, and the safety of the batteries can be improved; meanwhile, the base film layer is arranged in the middle area of the base film layer, damage to the edge and the overall structure of the base film can be avoided, the mechanical strength and integrity of the base film can be kept, damage or tearing of the base film caused by coating can be prevented, the coating process can be simplified, the cost can be reduced, and the base film layer is particularly suitable for large-size square batteries; and the problems of difficulty in electrolyte infiltration and poor conductivity of the center of a large-size square battery and lithium precipitation caused by insufficient electrolyte infiltration and poor dynamic performance of the center can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a diaphragm modifier, a high-wettability diaphragm, and a preparation method and application thereof. Background Art

[0002] The battery separator is one of the most important components in the battery. Its main function is to isolate the positive and negative electrodes of the battery, prevent the two electrodes from directly contacting and causing a short circuit, and allow lithium ions to pass freely between the two electrodes. The performance of the separator directly affects the overall performance of the battery, including the battery's energy density, cycle life and safety. With the development of battery technology, the performance requirements for separators are getting higher and higher, especially in the field of high energy density and high power density batteries, the requirements for the conductivity and wettability of separators are also getting higher and higher.

[0003] The existing solutions mainly improve the conductivity and wettability of the diaphragm by coating the surface of the diaphragm with conductive materials. For example, the conductivity of the diaphragm can be improved by coating the surface of the diaphragm with carbon materials, such as graphene, carbon nanotubes, etc. In addition, the wettability of the diaphragm can be improved by coating the surface of the diaphragm with polymer materials, such as polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), etc.

[0004] However, existing technologies have some problems and limitations in this field. First, although existing conductive materials, such as carbon materials, can improve the conductivity of the diaphragm, their conductivity is still limited and cannot meet the needs of high energy density and high power density batteries. Secondly, existing polymer materials, such as polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN), etc., although they can improve the wettability of the diaphragm, their hydrophilicity and mechanical properties are still not ideal and cannot meet the long-term use requirements of the battery. Especially for larger square batteries, the electrolyte diffuses from the surrounding to the center. When the wettability of the diaphragm to the electrolyte is not enough, the kinetic performance of the poorly infiltrated parts will be poor, and the lithium ions will not have time to embed, resulting in lithium precipitation; in addition, the existing coating structure leads to a complicated coating process, high cost, and difficulty in preparing modified materials, and high prices. Therefore, it is necessary to develop new structures and materials to solve these problems.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a diaphragm modifier, a high wettability diaphragm and a preparation method and application thereof, so as to at least solve any of the problems that the conductivity, hydrophilicity and mechanical properties of the existing diaphragms are not prominent, not combined and the modification cost is high. The high wettability diaphragm of the present invention adopts a diaphragm modifier of a composite material mixed with natural mineral clay sheets, one-dimensional conductive polymer materials and MXene to modify the base diaphragm (base membrane), which can not only meet the needs of high energy density and high power density batteries, but also meet the long-term use needs of the battery and improve the safety of the battery; at the same time, the composite material layer can be arranged in the middle area of ​​the base membrane layer, which can not only avoid damage to the edge and overall structure of the base membrane, maintain the mechanical strength and integrity of the base membrane, and prevent the base membrane from being damaged or torn due to coating, but also simplify the coating process and reduce costs, and is particularly suitable for large-sized square batteries, which can effectively improve the difficulty of electrolyte infiltration in the center of large-sized square batteries, poor conductivity, and lithium precipitation caused by insufficient electrolyte infiltration and poor kinetic performance in the center.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, a membrane modifier is provided, which is a composite material including natural mineral clay sheets, one-dimensional conductive polymer materials and MXene, wherein MXene is a two-dimensional nano-layered material composed of transition metal carbon / nitride.

[0009] Furthermore, the mass ratio of the natural mineral clay sheet, the one-dimensional conductive polymer material and the MXene is 1:(1-3):1.

[0010] Further, the one-dimensional conductive polymer material includes at least one of polypyrrole, polyaniline and poly(3,4-ethylenedioxythiophene);

[0011] and / or, the natural mineral clay flakes include at least one of montmorillonite, mica and kaolin;

[0012] And / or, the MXene includes Ti 3 C 2 T x 、Ti 3 C 2 、Ti 4 C 3 、V 2 C. Ta 4 C 3 T x or Nb 2 CT x , wherein T is a functional group, x satisfies the valence balance, and the functional group includes at least one of -O, -F, -Cl and -OH.

[0013] In a second aspect, a high wettability diaphragm includes a base membrane layer and a composite material layer bonded to the middle region on both sides of the base membrane layer along the thickness direction thereof, wherein the composite material layer includes the diaphragm modifier described in the first aspect.

[0014] Furthermore, the thickness of the composite material layer in the middle region on both sides of the base film layer along the thickness direction is equal, both of which are 5 to 11 μm.

[0015] Furthermore, the middle area is an area extending from the longest side direction to the shortest side direction of the largest surface of the base film layer, and occupies an area ratio of 45 to 55%.

[0016] Further, the base film layer includes a PP diaphragm or a PE diaphragm;

[0017] And / or, the composite material layer further comprises a binder;

[0018] And / or, the thickness of the base film layer is 12-20 μm;

[0019] And / or, the high wettability separator has a thickness of 20-40 μm.

[0020] In a third aspect, a method for preparing a high wettability diaphragm as described in the second aspect is provided, wherein the diaphragm modifier used to form the composite material layer is applied to the middle area on both sides of the base film layer along its thickness direction to obtain the high wettability diaphragm.

[0021] Furthermore, the application method is spraying, and a composite material formed by natural mineral clay sheets, one-dimensional conductive polymer materials and MXene is mixed with a binder in a solvent to form a slurry with a solid content of 20 to 50%, and then the slurry is sprayed at a spraying speed of 3 to 10 mm / s, first sprayed to the middle area on one side of the base film layer along its thickness direction, and then sprayed to the middle area on the other side of the base film layer along its thickness direction after drying.

[0022] In a third aspect, a high wettability separator as described in the second aspect or a high wettability separator prepared by the preparation method described in the third aspect is used as a battery separator.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The membrane modifier of the present invention proposes for the first time to compound one-dimensional conductive polymer materials such as polypyrrole (PPY), MXene and natural mineral clay flakes such as MMT materials. This combination can not only improve the conductivity and wettability of the membrane, but also improve its mechanical properties and thermal stability. Compared with existing carbon materials and general polymer materials, the conductivity, wettability and mechanical properties of one-dimensional conductive polymer materials and MXene materials are more superior. The addition of natural mineral clay flakes can further improve the wettability and significantly improve the thermal stability of the membrane, which can meet the needs of high energy density and long cycle batteries.

[0025] 2. The membrane modifier of the present invention can further reduce production costs by optimizing the doping ratio and coating thickness of one-dimensional conductive polymer materials, natural mineral clay sheets and MXene, and avoid negative impacts on other properties due to improved battery performance, such as reducing the energy density of the battery. This optimization method can achieve a balance between cost and benefit, improve production efficiency and reduce production costs.

[0026] 3. In the process of battery manufacturing, the present invention coats the composite material of one-dimensional conductive polymer material, natural mineral clay sheet and MXene in the middle area of ​​the diaphragm and places it in the center of the battery, which can effectively improve the difficulty of electrolyte infiltration and poor conductivity in the center of larger square batteries, and the lithium precipitation problem caused by insufficient electrolyte infiltration in the center. Compared with the existing coating position, the coating position of the present invention can not only avoid damage to the edge and overall structure of the base film, maintain the mechanical strength and integrity of the base film, prevent the base film from being damaged or torn due to coating, but also simplify the coating process and reduce costs.

[0027] 4. The high wettability diaphragm of the present invention can effectively improve the wettability, conductivity and thermal stability of the electrolyte at the center of the battery diaphragm without affecting the lithium ion transfer rate, thereby improving the cycle performance of the battery and avoiding negative effects on other properties due to improving battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is a schematic diagram of one side of the diaphragm modification of the present invention;

[0030] Figure 2 25℃1C charge-discharge cycle diagram for different embodiments and comparative examples. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0032] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0033] The object of the present invention is to provide a membrane modifier, a high wettability membrane and a preparation method and application thereof. Compared with the prior art, the high wettability membrane of the present invention adopts a natural mineral clay sheet, a one-dimensional conductive polymer material and MXene to be mixed as a membrane modifier of a composite material to modify the base membrane (base membrane), which can not only improve the conductivity and wettability of the base membrane, but also improve its mechanical properties and thermal stability. Compared with existing carbon materials and ordinary polymer materials, the conductivity, wettability and mechanical properties of one-dimensional conductive polymer materials such as polypyrrole (PPY) and MXene materials are more superior. The addition of natural mineral clay sheets such as montmorillonite (MMT) can significantly improve the thermal stability of the base membrane while further improving the wettability, which can meet the needs of high energy density, high power density, high safety and long cycle batteries. At the same time, the composite material can be coated in the middle area of ​​the base membrane, which can not only avoid damage to the edge of the base membrane and the overall structure, but also maintain the mechanical strength and integrity of the base membrane, prevent the base membrane from being damaged or torn due to coating, and simplify the coating process and reduce costs. Placing the high wettability diaphragm of the present invention in the center of the battery can effectively improve the problems of difficult electrolyte infiltration in the center of larger square batteries, poor conductivity, and lithium precipitation caused by insufficient electrolyte infiltration in the center, thereby improving the battery's cycle performance and safety performance, while avoiding negative effects on other performance (such as reducing the battery's energy density) due to improved battery performance.

[0034] The technical solution of the present invention is specifically as follows:

[0035] In a first aspect, a membrane modifier is provided, which is a composite material including natural mineral clay sheets, one-dimensional conductive polymer materials and MXene, wherein MXene is a two-dimensional nano-layered material composed of transition metal carbon / nitride.

[0036] The technical solution of the present invention mainly adopts the following technical means: First, abandon the carbon material and use the one-dimensional conductive polymer material as the first choice of the diaphragm modifier. Conductive polymer materials such as PPY themselves have high conductivity and hydrophilicity, which can effectively improve the wettability and conductivity of the electrolyte at the center of the battery diaphragm. Compared with ordinary conductive polymer materials, the one-dimensional conductive polymer material has better conductivity, and the transmission path of electrons in the tube or wire is more regular, which can effectively reduce resistance and improve conductivity. Due to the limitations of the preparation method and morphology of ordinary conductive polymer materials, the performance of its conductive properties may be affected to a certain extent. For example, the electron transmission inside the block conductive polymer material may be hindered by the disordered stacking of the molecular chain. In addition, the one-dimensional conductive polymer material of the present invention can also form a more stable structure with the flaky MXene, avoid the stacking of MXene sheets, better exert its conductivity, and at the same time replace most of the expensive MXene materials to modify the conductivity of the diaphragm. Second, a two-dimensional nano-layered material MXene composed of a transition metal carbon / nitride, i.e., a transition metal carbide and / or a transition metal nitride and / or a transition metal carbonitride, is selected, which has excellent electrical conductivity, high specific surface area and high electrical conductivity, has properties similar to graphene, and has excellent electrochemical and mechanical properties. Further, a MXene material with a unique organ structure can be selected, which has higher conductivity and stability and a larger specific surface area, and can significantly increase the transfer rate of lithium ions during charging and discharging. Because the specific surface area of ​​ordinary two-dimensional layered MXene mainly depends on the size and stacking method of the sheets, its specific surface area and porosity are smaller than those of the organ-shaped structure. The interlayer transmission of ions is mainly carried out in the channels between the two-dimensional planes, and the transmission path is relatively single, and the diffusion of ions perpendicular to the direction of the sheets may be subject to certain restrictions. The organ-shaped MXene: due to its special tubular structure, it has a larger specific surface area and higher porosity, and can provide more active sites. Its tubular structure provides a three-dimensional transmission channel for ions, and the ion diffusion path is more complex and diverse, which is conducive to accelerating the transmission and diffusion of ions. Third, natural mineral clay sheets with high heat resistance, such as montmorillonite, are selected to significantly improve the thermal stability of the diaphragm and prevent internal short circuits caused by shrinkage or melting of the diaphragm at high temperatures, thereby improving the safety of the battery. In addition, natural mineral clay sheets such as montmorillonite usually have layered or porous structures. These structures can adsorb ions in the electrolyte and provide attachment sites for the ions. Just like the small pores of a sponge can absorb and hold liquids, the structure of the clay sheet allows the components in the electrolyte to enter its interior, thereby showing affinity. Therefore, the introduction of natural mineral clay sheets can improve the affinity between the diaphragm and the electrolyte, and improve the liquid absorption rate and liquid retention capacity of the diaphragm, which is crucial to the performance and service life of the battery.Fourth, during the battery manufacturing process, a diaphragm coated with a composite material of a one-dimensional conductive polymer material, MXene, and natural mineral clay flakes can be placed in the center of the battery, which can effectively improve the problem of difficult electrolyte infiltration in the center of larger square batteries, poor conductivity, and lithium precipitation caused by insufficient electrolyte infiltration in the center. These four technical means can effectively improve the wettability and conductivity of the electrolyte in the center of the battery diaphragm, reduce the internal resistance of the battery, improve the rate and cycle performance of the battery, and reasonably control the cost.

[0037] As an optional embodiment of the diaphragm modifier of the present invention, the mass ratio of the natural mineral clay sheet, the one-dimensional conductive polymer material and the MXene is 1:(1-3):1, typically but not limitatively, 1:1:1, 1:1.5:1, 1:2:1, 1:2.5:1, 1:3:1, etc.

[0038] In the above technical scheme, the use of one-dimensional conductive polymer materials and MXene materials not only solves the problem that existing conductive materials such as carbon materials have limited ability to improve the conductivity of diaphragms and cannot meet the needs of high energy density and high power density batteries, but also solves the problem that the hydrophilicity and mechanical properties of existing polymer materials such as PVDF and PAN are still not ideal and cannot meet the long-term use requirements of batteries.

[0039] Furthermore, while solving the problems of the conductivity and hydrophilicity of the diaphragm, adding natural mineral clay flakes significantly improves the thermal stability of the diaphragm, preventing internal short circuits caused by shrinkage or melting of the diaphragm at high temperatures, thereby improving the safety of the battery.

[0040] Moreover, by optimizing the doping ratio of natural mineral clay sheets, one-dimensional conductive polymer materials and MXene, the effect equivalent to that of MXene modification alone can be achieved, which greatly reduces the use of MXene, a modified material with excellent electrochemical and mechanical properties but complex preparation and high price. This can reduce production and material costs, and avoid negative impacts on other properties due to improved battery performance, such as reducing the energy density of the battery or side reactions with the electrolyte.

[0041] As an optional embodiment of the membrane modifier of the present invention, the one-dimensional conductive polymer material includes at least one of polypyrrole, polyaniline and poly(3,4-ethylenedioxythiophene);

[0042] and / or, the natural mineral clay flakes include at least one of montmorillonite, mica and kaolin;

[0043] And / or, the MXene includes Ti 3 C 2 T x 、Ti 3 C2 、Ti 4 C 3 、V 2 C. Ta 4 C 3 T x or Nb 2 CT x , wherein T is a functional group, x satisfies the valence balance, and the functional group includes at least one of -O, -F, -Cl and -OH.

[0044] In a second aspect, a high wettability diaphragm includes a base membrane layer and a composite material layer bonded to the middle region on both sides of the base membrane layer along the thickness direction thereof, wherein the composite material layer includes the diaphragm modifier described in the first aspect.

[0045] As an optional embodiment of the high wettability diaphragm of the present invention, the thickness of the composite material layer in the middle area on both sides of the base film layer along its thickness direction is equal, both of which are 5 to 11 μm (such as 6 μm, 7 μm, 8 μm, 9 μm, 10 μm).

[0046] In the above technical scheme, the composite material layers on both sides of the high wettability diaphragm serve as modification layers, and their thickness is the same. The thickness of each composite material layer is controlled to be 5 to 11 μm to avoid the influence of the modification layer being too thin or too thick. If it is too thin, firstly, it cannot effectively inhibit the growth of dendrites and cannot provide sufficient protection for the diaphragm. During the assembly or use of the battery, the diaphragm is easily damaged by physical effects such as wear and extrusion of the electrode material, thereby affecting the battery performance and life; secondly, it will cause insufficient ion conduction stability. The thin modification layer is difficult to ensure the stability and uniformity of the ion conduction channel. As the charge and discharge cycle proceeds, the ion conduction path may be interrupted or changed, resulting in an increase in the internal resistance of the battery, an increase in polarization phenomenon, and a reduction in the battery charge and discharge efficiency and rate performance; thirdly, it may lead to poor interface compatibility. A too thin modification layer is difficult to form a good interface contact between the diaphragm and the electrode, which is not conducive to charge transfer and ion transmission between the electrode and the diaphragm, affecting the overall performance of the battery. If it is too thick, firstly, the thickness of the diaphragm modification layer will hinder ion transmission, increase the resistance of ion migration, make ion transmission inside the battery difficult, and reduce the battery's charge and discharge efficiency and rate performance; secondly, the bonding force between the thicker modification layer and the diaphragm matrix may become weaker. During the battery charge and discharge process, due to factors such as the volume change of the electrode material, the modification layer is prone to fall off and cracks, which will lead to a decline in battery performance or even failure; thirdly, the thickness of the modification layer will increase the overall mass and volume of the diaphragm. For batteries pursuing high energy density, this will to a certain extent offset the advantages of the battery itself due to the use of high energy density electrode materials, and reduce the overall energy density of the battery.

[0047] As an optional embodiment of the high wettability diaphragm of the present invention, the middle region is a region extending along the longest side direction of the largest surface of the base film layer toward the shortest side direction, and the area ratio is 45-55% (such as 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%), and further 50%.

[0048] As an optional embodiment of the high wettability separator of the present invention, the base film layer includes a PP separator or a PE separator;

[0049] And / or, the composite material layer further includes a binder, and further, the mass ratio of the binder to the composite material is 5-20:80-95 (such as 5:95, 7:93, 10:90, 13:87, 15:85, 17:83, 20:80).

[0050] In the above technical solution, in addition to the various materials listed therein, other materials with equivalent performance may also be used, which are not listed one by one. Moreover, the various materials listed above can still be used for modifying the diaphragm of the present invention after various modifications. In addition, the various materials listed above can be obtained by various existing preparation methods, or can be directly commercially obtained.

[0051] As an optional embodiment of the high wettability separator of the present invention, the thickness of the base film layer is 12-20 μm (such as 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm);

[0052] And / or, the thickness of the high wettability separator is 20-40 μm (e.g., 21 μm, 23 μm, 25 μm, 27 μm, 29 μm, 31 μm, 33 μm, 35 μm, 37 μm, 39 μm).

[0053] In a third aspect, a method for preparing the high wettability diaphragm of the second aspect is provided, wherein the diaphragm modifier used to form the composite material layer is applied to the middle area on both sides of the base film layer along the thickness direction thereof to obtain the high wettability diaphragm.

[0054] As an optional embodiment of the preparation method of the present invention, the application method is selected from one of spraying, spin coating, casting, drip coating and scraping. Further, the application method is spraying, mixing the composite material formed by natural mineral clay sheets, one-dimensional conductive polymer materials and MXene with a binder in a solvent to form a slurry with a solid content of 20-50% (such as 25%, 30%, 35%, 40%, 45%), and then spraying the slurry at a spraying speed of 3-10mm / s, first spraying to the middle area of ​​the base film layer along one side of its thickness direction, and then spraying to the middle area of ​​the base film layer along the other side of its thickness direction after drying.

[0055] In the above technical solution, the slurry is sprayed on both sides of the diaphragm by spraying. Compared with other methods, such as electrodeposition, sol-gel, spin coating, casting, drip coating and scraping, the operation is simpler, the cost is relatively low, and it is more suitable for large-scale production. Optionally, the spraying speed is 3-10mm / s, such as 4mm / s, 6mm / s, 8mm / s, 10mm / s; Optionally, the spraying speed of the composite material layer on both sides of the base film layer is the same or different. Optionally, after spraying one side of the composite material layer, it is dried and dried, and the drying temperature is 50-80℃, such as 55℃, 60℃, 65℃, 70℃, 75℃, and the drying time is 4-12h, such as 5h, 7h, 9h, 11h.

[0056] In addition, the solid content of the composite material in the slurry is controlled within the range of 20-50% to avoid the influence of excessive or too low solid content, such as the influence of excessive solid content: 1. The fluidity deteriorates. If the solid content is too high, the viscosity of the slurry will increase significantly, and the fluidity will decrease, which will make it difficult for the slurry to spread evenly during the coating process, affecting the consistency of the diaphragm, and then affecting the performance consistency of the battery. 2. When coating the high-solid content slurry, problems such as uneven coating thickness and uneven surface may occur. In severe cases, it may even clog the coating head, affecting production efficiency and product quality. The influence of too low solid content: 1. The blocking effect is poor. If the solid content is too low, it is difficult to effectively block the growth of lithium dendrites. Dendrites may penetrate the diaphragm, causing internal short circuits in the battery, reducing the coulomb efficiency of the battery, rapidly decaying the capacity, and even causing safety hazards such as thermal runaway. 2. The mechanical properties are insufficient, and it is impossible to provide sufficient strength and toughness support for the diaphragm. The diaphragm is easily damaged or punctured by external forces during battery assembly or use, resulting in short circuits of the positive and negative electrodes, which seriously affects the safety and reliability of the battery. 3. The drying energy consumption increases. The low solid content means that the solvent content in the slurry is high. In the drying process after coating, more energy is required to evaporate the solvent, which increases the production cost, prolongs the drying time, and reduces the production efficiency.

[0057] In a fourth aspect, a high wettability separator according to the second aspect or a high wettability separator prepared by the preparation method according to the third aspect is used as a battery separator.

[0058] Since the diaphragm of the present invention has excellent affinity, conductivity, mechanical properties and thermal stability, it can be used as a battery diaphragm, especially in large-sized square batteries, to meet the needs of long-term and efficient operation of the battery, so it can be used in the field of electric vehicles or energy storage systems.

[0059] Specifically, the battery is a lithium battery (lithium ion battery), which further includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode active material, and further optionally, the positive electrode active material includes LiFePO 4The negative electrode comprises a negative electrode active material, and further optionally, the negative electrode active material comprises graphite; the electrolyte comprises a lithium salt and a solvent, and further optionally, the lithium salt comprises LiPF 6 , the concentration of the lithium salt is 1M. Further optionally, the solvent includes at least one of ethylene carbonate (EC) and dimethyl carbonate (DMC); further optionally, the solvent includes ethylene carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1.

[0060] The present invention will be further described below with reference to specific embodiments and comparative examples.

[0061] Each embodiment and comparative example is mainly based on polypyrrole (PPY), MXene (Ti 3 C 2 T x , T is at least one of the functional groups -O, -F, -Cl and -OH) and one or more of montmorillonite (MMT) as a diaphragm modifier to modify the battery diaphragm, and the specific steps include the following:

[0062] Step 1: Preparation of PPY materials. Polypyrrole nanotubes / wires were successfully synthesized through a self-assembly process. Methyl orange, a very cheap azo dye molecule with a sulfonate group, was used as a dopant. While pyrrole was polymerizing, methyl orange as a dopant preferentially formed a fibrous complex with the oxidant ferric chloride; pyrrole monomers polymerized on the template surface formed by the methyl orange / ferric chloride complex. 3+ The template is reduced and self-degraded, and finally, the specific polypyrrole nanotubes / wires can be obtained without removing the template. Specifically, take 200ml of 0.005mol / L methyl orange solution, add 30ml of 0.162g (1mmol) FeCl 3 Aqueous solution, flocculent precipitate is formed immediately. Add 0.7mL pyrrole to the system, stir and react at room temperature for 24h, and wash with distilled water, acetone and ethanol respectively by vacuum filtration until the filtrate is colorless. Dry in a vacuum oven at 60℃ for 12 hours to obtain a black polymer powder, which is PPY.

[0063] Step 2: Preparation of MXene material. 3 AlC 2 ) was slowly added to the HF solution, with the mass ratio of MAX powder to HF solution being 1:5, and then stirred at 60 °C for 24 hours. The reaction solution was washed several times with deionized water until the pH value reached 6, and the deposit was dried in a vacuum oven at 50 °C for 8 hours to obtain MXene powder (TiO2 with organ structure). 3 C 2 T x ).

[0064] Step 3: Select one or more of PPY, MXene and MMT materials as membrane modifiers for slurry preparation and spraying to modify the base membrane. 3 C 2 T x With MMT in a certain mass ratio (such as MMT:PPY:Ti 3 C 2 T x =1:1:1 or 1:2:1 or 1:3:1) and then sprayed on the middle area on both sides of the PP / PE base film, such as Figure 1 Specific steps: According to the mass ratio of the diaphragm modifier (such as PPY, Ti 3 C 2 T x and MMT composite material): binder (PVDF) = 8:2, mix well and add NMP to make slurry for use, the solid content of the slurry is 30%. Then spray the prepared slurry on the center of one side of the base film at a spraying speed of 3-10mm / s, the area ratio is 50%, the thickness is 4-12μm, dry at 50℃ for 6h, and then spray the center of the other side of the base film in the same way, the area ratio is 50%, the thickness is 4-12μm, such as Figure 1 The thickness of the base film is 12-20 μm, and the thickness of the high wettability diaphragm obtained after the base film is modified on both sides by the composite material is 20-40 μm.

[0065] Example 1

[0066] The above modification process is used to obtain a high wettability diaphragm, wherein the base film layer is a PP diaphragm with a thickness of 12 μm; in the composite material layer, the diaphragm modifier is MMT:PPY:Ti 3 C 2 T x =3.333g:3.333g:3.333g, the thickness of the composite material layers on both sides of the base membrane layer is 8μm respectively.

[0067] Example 2

[0068] The only difference from Example 1 is that the membrane modifier is MMT:PPY:Ti 3 C 2 T x =2.5g:5g:2.5g, and the rest of the settings are the same.

[0069] Example 3

[0070] The only difference from Example 1 is that the membrane modifier is MMT:PPY:Ti 3 C 2 T x=2g:6g:2g, and the rest of the settings are the same.

[0071] Comparative Example 1

[0072] The only difference from Example 1 is that a blank diaphragm is used, that is, no diaphragm-modifying material is sprayed on both sides.

[0073] Comparative Example 2

[0074] The only difference from Example 1 is that the membrane modifier is 10 g PPY, and the other settings are the same.

[0075] Comparative Example 3

[0076] The only difference from Example 1 is that the membrane modifier is 10 g Ti 3 C 2 T x , the rest of the settings are the same.

[0077] Comparative Example 4

[0078] The only difference from Example 1 is that the membrane modifier is MMT:PPY=5g:5g, and the other settings are the same.

[0079] Comparative Example 5

[0080] The only difference from Example 1 is that the membrane modifier is PPY:Ti 3 C 2 T x =5g:5g, and the rest of the settings are the same.

[0081] Comparative Example 6

[0082] The only difference from Example 1 is that the membrane modifier is MMT:Ti 3 C 2 T x =5g:5g, and the rest of the settings are the same.

[0083] Comparative Example 7

[0084] The only difference from Example 1 is that the composite material layers on both sides of the base film layer are 12 μm thick respectively, and the other settings are the same.

[0085] Comparative Example 8

[0086] The only difference from Example 1 is that the composite material layers on both sides of the base film layer are 4 μm thick respectively, and the other settings are the same.

[0087] Comparative Example 9

[0088] The only difference from Example 1 is that the PPY in the membrane modifier is not a one-dimensional structure (purchased from Alpha (Zhengzhou), product CAS No.: 30604-81-0; molecular formula: C 4 H 5 N, molecular weight: 67.08%, purity 98%; grade: industrial grade), and the rest of the settings were the same.

[0089] Application and testing

[0090] 1. The diaphragms obtained in the examples and comparative examples were tested as follows:

[0091] First, the contact angle test of the electrolyte is performed on the aforementioned diaphragm. The specific steps are as follows: 1. Place the diaphragm sample flat on the stage of the contact angle meter to ensure that the sample surface is flat and wrinkle-free. 2. Use a chamfered glass dropper or the automatic dropper equipped with the contact angle meter to drop a drop of electrolyte (containing 1M LiPF 6 3. Use the camera or imaging system of the contact angle meter to collect images of the droplets on the surface of the diaphragm, and then use the instrument software to automatically fit the contact angle value with one click; record the contact angle value obtained from each measurement, repeat the test multiple times, and take the average value to reduce the error. The smaller the contact angle between the diaphragm and the electrolyte, the better the wettability of the electrolyte and the diaphragm.

[0092] Secondly, the surface resistance test of the above-mentioned diaphragm is carried out. The specific steps are as follows: 1. Place the diaphragm sample on the test bench of the instrument (BER1030 of Yuanneng Technology). 2. Set the pressure to 0.5-1MPa and hold the pressure for about 15s. 3. Record the value obtained by the instrument each time, repeat the test several times and take the average value to reduce the error. The smaller the surface resistance, the better the conductivity of the diaphragm.

[0093] Then, the aforementioned diaphragm is tested for heat shrinkage in the longitudinal direction (MD) and transverse direction (TD). The specific steps are as follows: 1. Mark the diaphragm sample with transverse and longitudinal labels and clamp it to the Labthink instrument. 2. Set the temperature to 130℃ for 1 hour. The instrument automatically records and analyzes the data through sensors. The smaller the heat shrinkage of the diaphragm, the better. If the heat shrinkage is too large, when the temperature rises, the diaphragm will shrink excessively, which may cause the positive and negative electrodes to contact, causing a short circuit, causing battery failure, and even safety problems such as overheating, fire, explosion, etc.

[0094] Finally, the puncture strength of the aforementioned diaphragm is tested. The specific steps are as follows: 1. Place the diaphragm sample in the fixture of the electronic universal testing machine. 2. Set the test speed to (50±5) mm / min, the test temperature to room temperature 25°C, and record the data displayed on the instrument after starting the test. The greater the puncture strength, the better. A high puncture strength can better resist the puncture of the sharp parts of the electrode material or foreign objects that may occur during battery assembly and use, thereby maintaining the integrity of the diaphragm, avoiding short circuits between the positive and negative electrodes, and ensuring safe and stable operation of the battery. In addition, in lithium-ion batteries, a diaphragm with a strong puncture strength can prevent dendrites from piercing the diaphragm, thereby improving the safety and service life of the battery.

[0095] 2. Apply the above-mentioned separator to the battery and test the battery performance:

[0096] The separators obtained in the examples and comparative examples were applied to large-sized square batteries (thickness 44 mm, width 210 mm, height 238 mm). Specifically, the separators were assembled into the batteries, wherein LiFePO 4 As the positive electrode material, LiFePO 4 : The mass ratio of conductive carbon black SP: PVDF is 97:2:1. Graphite is used as the negative electrode material. The mass ratio of graphite: conductive agent SP: CMC powder: SBR in the negative electrode is 96.5:0.5:1.2:1.8. 1M LiPF 6 Ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio of 1:1) are used as electrolyte to obtain a lithium iron phosphate battery.

[0097] The aforementioned lithium iron phosphate battery was subjected to a cycle test of 1C charge and 1C discharge at 25°C using Xinwei testing equipment, and the capacity retention rate data of the aforementioned lithium iron phosphate battery after 400 cycles was recorded. The higher the capacity retention rate, the better. A high capacity retention rate means that during use, the battery can maintain a high power storage capacity for a long time.

[0098] The battery was then disassembled to observe the interface state of the negative electrode. The absence of lithium precipitation at the interface indicates that lithium ions can be normally embedded and extracted from the negative electrode material. This helps maintain the battery's cycle life and stable charge and discharge performance, allowing the battery to work efficiently for a long time.

[0099] The above test results are shown in Table 1:

[0100] Table 1 Comparison of relevant properties of comparative examples and embodiments

[0101]

[0102] As shown in Table 1, Examples 1 to 3 use PPY and Ti 3 C2 T x The wetting angle of the diaphragm modified with the MMT composite material in contact with the electrolyte is much smaller than the contact angle of the unmodified diaphragm in Comparative Example 1, and its surface resistance, MD thermal shrinkage, TD thermal shrinkage and puncture strength are also better than those of the unmodified Comparative Example 1. It can be seen that the diaphragm modified with the composite material layer of the present invention has good affinity, conductivity, mechanical properties and thermal stability. After the diaphragms obtained in Examples 1 to 3 are applied to large square batteries, the capacity retention rate of the battery after 400 cycles is also higher than that of Comparative Example 1, and there is no lithium precipitation phenomenon on the disassembled interfaces. It can be seen that the battery using the diaphragm of the present invention has the ability to work efficiently for a long time.

[0103] Moreover, the capacity retention rate of the battery in Example 1 is better than that in Comparative Example 2, and equivalent to that in Comparative Example 3, indicating that mixing PPY, MMT and MXene in a certain proportion can achieve a better effect equivalent to that of pure MXene. Since MMT is cheap and the preparation process of PPY is simple and low-cost, the production cost can be greatly reduced while achieving a similar effect to that in Comparative Example 3. In particular, the composite material layer in the diaphragm of Example 1 has a conductive effect equivalent to that of a pure MXene layer, and has better mechanical properties and thermal stability, and higher safety and stability. As a battery diaphragm, it is more suitable for application fields such as electric vehicles and energy storage systems, because the ion conductivity of the diaphragm is enhanced, which can make the transmission of charge carriers such as lithium ions smoother and more efficient during the charging and discharging process of the battery, thereby reducing the internal resistance of the battery, reducing the energy loss of the battery during the charging and discharging process, and improving the charging and discharging efficiency and rate performance of the battery, so that the battery can output a larger current to meet the needs of high-power equipment; and the diaphragm with good ionic conductivity can make the battery more fully utilize the electrode material in a limited space, store and release more electrical energy, thereby improving the energy density of the battery, so that the battery can provide a longer driving range or higher power output at the same volume or weight, which is particularly critical for application scenarios such as electric vehicles that have high requirements for endurance. Good ion conductivity of the diaphragm helps maintain the uniform distribution of the electric field inside the battery, reduces the phenomenon of excessive local current density, thereby reducing the polarization degree of the electrode material during the charge and discharge process, reduces the structural damage of the electrode material and the shedding of active substances, enables the battery to withstand more charge and discharge cycles, and extends the battery life. Enhancing the ion conductivity of the diaphragm can reduce the internal resistance of the battery, reduce the heat generated by the battery during the charge and discharge process, and reduce the risk of thermal runaway. Compared with methods such as optimizing the pore structure of the diaphragm to improve the ion conductivity of the diaphragm, it can also enhance the mechanical strength and thermal stability of the diaphragm, prevent the diaphragm from rupturing or shrinking at high temperature or high current density, and avoid safety problems such as short circuits caused by direct contact between the positive and negative electrodes.

[0104] In addition, the contact angles of the electrolytes of Examples 1 to 3 and Comparative Examples 2 to 3 are not much different, and are slightly smaller. This is because PPY and MXene, in addition to being conductive, also have a certain hydrophilicity, which enables the electrolyte to wet the diaphragm to a certain extent, and the addition of montmorillonite makes it easier for the composite material layer to wet the diaphragm, thereby improving the battery's ability to retain liquid, improving the ion transmission efficiency in the diaphragm and the uniformity of battery charge and discharge, and improving the battery's cycle performance.

[0105] Compared with Example 1, the contact angle and surface resistance of the diaphragms of Comparative Examples 4 to 6 are significantly worse than those of Example 1, which indicates that the composite of the two materials cannot better demonstrate the wettability and conductivity of the materials. Moreover, the battery capacity retention rates of Comparative Examples 4 to 6 are not as good as that of Example 1. There is a slight lithium deposition phenomenon at the disassembly interface of the batteries obtained in Comparative Examples 4 and 6, which is due to the fact that the conductivity of the two-component composite material is worse than that of Example 1.

[0106] Compared with Example 1, Comparative Examples 7 and 8 changed the thickness of the diaphragm modification layer, and the contact angle was not much different. When the modification layer was thick, the contact angle was a little smaller, and the thermal shrinkage performance and puncture performance were enhanced, but the surface resistance increased. At the same time, the capacity retention rate of the batteries obtained in Comparative Examples 7 and 8 was lower than that in Example 1, indicating that the coating layer was too thick or too thin, which was not conducive to the overall cycle performance of the battery. There was a slight lithium precipitation phenomenon at the disassembly interface, which should be related to the coating thickness.

[0107] Compared with Example 1, the PPY in Comparative Example 9 is a non-one-dimensional structure, and its surface resistance and contact angle are greater than those in Example 1. It can be seen that its conductivity and affinity are worse than those in Example 1. The capacity retention rate of the battery obtained in Comparative Example 9 is lower than that in Example 1, and there is a slight lithium deposition phenomenon at the disassembly interface, which should be related to the shape of PPY.

[0108] In summary, the technical solution of the present invention is advanced and can be widely used in application fields such as battery manufacturing, electric vehicles, and energy storage systems. First, the technical solution of the present invention can effectively improve the wettability, conductivity, and thermal stability of the electrolyte at the center of the battery diaphragm, thereby increasing the transfer speed of lithium ions during the charging and discharging process of the battery, and improving the cycle performance of the battery; improving the difficulty of electrolyte infiltration in the center of larger square batteries, and the lithium precipitation problem caused by insufficient electrolyte infiltration in the center, and improving the uniformity of battery charging and discharging, which is of great significance to the field of battery manufacturing. Secondly, with the rapid development of the electric vehicle market, the performance requirements for batteries are getting higher and higher. The technical solution of the present invention can effectively improve the performance of batteries and meet the needs of electric vehicles for batteries. Finally, as an important part of new energy, the energy storage system also has high requirements for the performance of batteries. The application of the technical solution of the present invention can improve the efficiency and stability of the energy storage system and promote the development of new energy. Therefore, the technical solution of the present invention has broad market demand and good application prospects.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A membrane modifier, characterized in that: The membrane modifier is a composite material, including natural mineral clay flakes, one-dimensional conductive polymer materials and MXene, wherein MXene is a two-dimensional nano-layered material composed of transition metal carbon / nitride.

2. The membrane modifier according to claim 1, characterized in that: The mass ratio of the natural mineral clay sheet, the one-dimensional conductive polymer material and the MXene is 1:(1-3):

1.

3. The membrane modifier according to claim 1, characterized in that: The one-dimensional conductive polymer material includes at least one of polypyrrole, polyaniline and poly(3,4-ethylenedioxythiophene); and / or, the natural mineral clay flakes include at least one of montmorillonite, mica and kaolin; And / or, the MXene comprises Ti3C2T x , Ti3C2, Ti4C3, V2C, Ta4C3T x or Nb2CT x , wherein T is a functional group, x satisfies the valence balance, and the functional group includes at least one of -O, -F, -Cl and -OH.

4. A high wettability diaphragm, characterized in that: It comprises a base membrane layer and a composite material layer bonded to the middle regions on both sides of the base membrane layer along the thickness direction thereof, wherein the composite material layer comprises the diaphragm modifier according to any one of claims 1-3.

5. The high wettability diaphragm according to claim 4, characterized in that: The thickness of the composite material layer in the middle regions on both sides of the base film layer along the thickness direction is equal, both of which are 5 to 11 μm.

6. The high wettability diaphragm according to claim 4, characterized in that: The middle area is an area extending from the longest side direction to the shortest side direction along the largest surface of the base film layer, and occupies an area ratio of 45 to 55%.

7. The high wettability diaphragm according to claim 4, characterized in that: The base film layer includes a PP diaphragm or a PE diaphragm; And / or, the composite material layer further comprises a binder; And / or, the thickness of the base film layer is 12-20 μm; And / or, the high wettability separator has a thickness of 20-40 μm.

8. A method for preparing a high wettability diaphragm according to any one of claims 4 to 7, characterized in that: The membrane modifier used to form the composite material layer is applied to the middle areas on both sides of the base film layer along the thickness direction to obtain the high wettability membrane.

9. The preparation method according to claim 8, characterized in that: The application method is spraying, mixing a composite material formed by natural mineral clay sheets, one-dimensional conductive polymer materials and MXene with a binder in a solvent to form a slurry with a solid content of 20-50%, and then spraying the slurry at a spraying speed of 3-10 mm / s, first spraying it to the middle area on one side of the base film layer along its thickness direction, and then spraying it to the middle area on the other side of the base film layer along its thickness direction after drying.

10. Use of the high wettability separator according to any one of claims 4 to 7 or the high wettability separator prepared by the preparation method according to any one of claims 8 to 9 as a battery separator.

Citation Information

Patent Citations

  • Battery separator, preparation method thereof and lithium ion battery

    CN112117420A

  • Kaolin coating lithium ion battery diaphragm

    CN115642368A

  • Diaphragm for secondary ion battery as well as preparation method and application of diaphragm

    CN116706430A

  • Diaphragm, preparation method thereof and lithium battery

    CN119108759A

  • Electrochemical device

    US20210057700A1